Validating DFS concept in lifecycle subway projects in China based on incident case analysis and network analysis - Xiahou, Xiaer; Yuan, Jingfeng; Li, Qiming; Skibniewski, Miroslaw J. (Journal of Civil Engineering and Management, 2018)
Regardless of potential benefits of design for safety (DFS) concept for lifecycle safety management in construction industry, DFS adoption as an early intervention has been slower than expected. While existing research mainly concentrates on construction and operation phases, the role of design phase in construction safety management is always ignored. To validate the influence of DFS concept on lifecycle safety performance, this research conducted an incident case analysis (ICA) based on 442 cases collected from lifecycle subway projects, and a subway design-incident classification model (SDICM) was developed to help identify their relationship to DFS concept. Network theory was applied to study the interdependence of 22 subsystems obtained from China’s code for metro design in lifecycle safety performance. Research findings show 236 out of 442 accidents are linked to DFS. Compared with construction phase, operation phase is more susceptible to design work. Station Building (SB), Section Construction (SC), Platform Screen Doors (PSD), Vehicle Systems (VES) and Power Supply Systems (PSS) are identified as having the highest number of accidents. The results of network analysis are consistent with ICA and demonstrate the safety interdependence of subsystems. This research can help improve the cognizance of DFS, and the identified subsystems should be given priority in the design phase.